Delimitación y caracterización morfométrica del área metropolitana de Valencia - Julia Salom-Carrasco; Isabelle Thomas; Gaëtan Montero (Cybergeo, 2021)
This paper aims at proposing a new delimitation of the morphological agglomeration of Valencia (Spain) using a method based on fractal geometry (MorphoLim) and comparing the obtained results with standard delineations.  The urban agglomeration of Valencia is located on the Mediterranean coast and is experiencing a strong urban growth by spatial dispersion and by multiplication of building floors. The originality of this paper lies in the application of a method capable of taking into account the diffusion for several heights of buildings, which allows to take into account the specificities of Valencia.   The introduction of the third dimension offers a new perspective in the morphological analysis of urban spaces.